Best Answer

x2-10 = 4x+11

x2-4x-10-11 = 0

x2-4x-21 = 0

(x+3)(x-7) = 0

x = -3 and x = 7

User Avatar

Wiki User

โˆ™ 2011-10-21 09:55:12
This answer is:
User Avatar
Study guides


20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

See all cards
2024 Reviews

Add your answer:

Earn +20 pts
Q: How do you solve for the problem x squared minus 10 equals 4x plus 11?
Write your answer...
Still have questions?
magnify glass
Related questions

How do you solve 16t squared minus 9 equals 0?

Solve this problem -x squared -40x- 80 =0

How do you solve X squared minus four for x equals 3?

Your Problem: X - 4 = ?Current Problem: 3 [squared] - 4 = ?How: When a numbered is squared, it means you multiply it against itself. So, 3 squared equals 3x3.3x3 = 9So, you would then take 9 and minus it by 4, which would than equal 5.Answer:3 [squared] - 4 = 5or9 - 4 = 5

Can you solve x squared minus six plus five equals zero?


How do you solve 0 equals x squared minus ten x plus 16?

Solve using the quadratic formula

How do you solve x squared minus 10 equals 0?

If x squared -10 = 0 then x = the square root of 10

X squared plus y squared minus 1 all cubed then minus the product of x squared times y cubed that all equals 0 How do you solve for y?

You have to put your heart into it!

How do you solve this a squared minus b squared plus ac minus bc?


How do you solve x squared minus 4 y squared?

It is not clear what you want to solve for.

How do you solve 5x-to-the-4th minus 483x-cubed plus 94x-squared plus 126x minus 18 equals 0?


How do you solve 3x squared plus 5x minus 25 equals 0?

x = 25 / 3squared + 5

How do you solve x squared minus x minus twelve by Euclid?

Without an "equals" word or sign somewhere, there is nothing to solve.You only have an expression, not an equation.

How would you solve x squared minus two x minus three equals zero?

That factors to (x + 1)(x - 3) x = -1, 3

People also asked